'The unbreakable solidarity of women throughout the world with heroic Vietnam': Freda Brown, women's organisations and the anti-Vietnam War movement. Issue 2 (3rd April 2018) - Milner, Lisa
Abstract: One of the many Australians who campaigned against participation in the Vietnam War was Freda Brown (1919–2009). Among the anti-war groups she worked within, three employed a maternalist approach to many of their campaigns. Mobilising against the prevailing concept of a woman's role to keep the home fires burning and support the troops, Brown travelled to North Vietnam at the height of the conflict. One remarkable outcome of her activism was the funding of the Hanoi Obstetrics and Gynaecology Hospital. This article explores Brown's work in these organisations, and examines her work in transnational maternalism.